Poor cow - Dunn, Nell 1936-; Donovan 1946- (Momentum Pictures, 2001)
Details the dismal life of a young woman trying to cope in squalor while her husband is in jail. Clutching at any slight chance of happiness she has an affair with his best friend with disastrous consequences.
Original: Großbritannien 1967
Bildformat 1.66:1
Keywords: Feature films; Film; DVD-Video